2015
DOI: 10.1016/j.rmcr.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal epithelial-myoepithelial carcinoma associated with sarcoid-like reaction: A case report

Abstract: Epithelial-myoepithelial carcinomas are rare tumors that primarily originate in the salivary glands but have also been found in the tracheobronchial tree. We report the first case of epithelial-myoepithelial carcinoma associated with sarcoidosis. A 61 year old Hispanic man presented with altered mental status and hypercalcemia. Imaging revealed diffuse intra-thoracic and intra-abdominal lymphadenopathy. A diagnostic bronchoscopy was performed where an incidental tracheal nodule was discovered and biopsied. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Besides diagnosis, the treatments of tracheal tumor remained controversial. Although case reports, reviews and surgical techniques of tracheal tumor have been published, neither large‐scale retrospective studies has been reported, nor consensus on whether they should be treated by the thoracic surgeon or head and neck surgeon has been reached. Even if the surgical treatments has been applied, they would be various without any standard due to the absence of classification.…”
Section: Discussionmentioning
confidence: 99%
“…Besides diagnosis, the treatments of tracheal tumor remained controversial. Although case reports, reviews and surgical techniques of tracheal tumor have been published, neither large‐scale retrospective studies has been reported, nor consensus on whether they should be treated by the thoracic surgeon or head and neck surgeon has been reached. Even if the surgical treatments has been applied, they would be various without any standard due to the absence of classification.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary epithelial-myoepithelial Carcinoma are very rare. Because of their origin from the tracheobronchial submucosal glands, pulmonary Epithelial-Myoepithelial Carcinoma are often central lesions that present as endobronchial tumor masses [7][8][9][10][11][12]. As a result, patients commonly present with signs and symptoms of bronchial obstruction, including shortness of breath, cough, hemopt-ysis, chest pain, fever, or pneumonia [13].…”
Section: Discussionmentioning
confidence: 99%